Occurrence of noroviruses in recycled water and sewage sludge: emergence of recombinant norovirus strains - L. Kittigul (2019)
© 2019 The Society for Applied Microbiology Aims: To investigate the presence of noroviruses in recycled water and sewage sludge obtained from a wastewater treatment plant in Bangkok Metropolitan Region, Thailand. Methods and Results: Twenty-seven recycled water and twenty-three sewage sludge samples were tested for the presence of norovirus genogroup (G)I and GII using RT-nested PCR. Molecular characterization of noroviruses was undertaken by DNA sequencing and phylogenetic analysis. The level of the RNA genome of the noroviruses was determined using quantitative real-time RT-PCR. Noroviruses were detected in 44·4% of recycled water samples and 73·9% of sewage sludge samples. Norovirus GI.2 and GII.4 were identified in recycled water samples at levels of 2·19 × 10 1 and 3·26 × 10 4 RNA copies per litre. Six different genotypes of GI (GI.1, GI.2, GI.5a, GI.5b, GI.6b and GI.7) and GII.17 were identified in sewage sludge samples at levels ranging from 1·99 × 10 1 –1·43 × 10 5 RNA copies per gram wet weight. Four recombinant norovirus strains were detected in sewage sludge samples, namely GII.P16-GII.2, GII.P16-GII.4, GII.P16-GII.13 and GII.P21-GII.13. Conclusions: These findings provide evidence that noroviruses may be spread to the community and environment via the use of recycled water for plant areas, and sewage sludge for land application. Significance and Impact of the Study: This is the first study demonstrating recombinant norovirus strains in sewage sludge samples. The presence of noroviruses in recycled water and sewage sludge contributes to a health risk of environmental exposure.